The Effect of Tourist Attractions, Destination Branding and Tourism Education on the Sustainability of Mangrove Ecotourism - Izzah, Nurul; Islam, Darul (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Ecotourism is a form of tourism that emphasizes sustainability principles, aiming to protect the environment and enhance the welfare of surrounding communities. This concept has become increasingly important with the growing awareness of ecosystem security, particularly the mangrove ecosystem. The development of mangrove ecotourism in Lembung Village, which is rich in resources and has significant potential to be established as a sustainable ecotourism destination, underscores this importance. This study aims to determine whether tourist attractions, destination branding, and tourism education affect the sustainability of mangrove ecotourism in Lembung Pamekasan. A quantitative methodology was used in this research. The study population consisted of residents of Lembung Village and visitors to the mangrove area in Lembung Pamekasan. The research sampled 90 respondents selected through a purposive non-probability sampling method. Data exploration was conducted using SPSS 26. The results indicate that the sustainability of mangrove ecotourism in Lembung Pamekasan is positively and significantly influenced by the three independent variables. Collectively, these independent factors have a simultaneous impact on the long-term sustainability of mangrove ecotourism.